Examination of gestational diabetes mellitus at a tertiary care hospital - Gunjan; Khare, Indu; Kumar, Ashutosh; Sinha, Anjana (International Journal of Research in Medical Sciences, 2024)
Background: Globally, 14% of pregnancies are complicated by gestational diabetes mellitus (GDM). This can induce type 2 diabetes and metabolic problems in mothers and children. Dietary and lifestyle adjustments are the basic GDM treatments, but optimal euglycemia treatments are being researched. The study examined GDM prevalence and implications in pregnant women and compared mother and foetal outcomes in GDM patients and controls. Methods: The study involved 200 pregnant females, with 100 diagnosed with GDM and 100 as controls. Data were gathered through glucose challenge tests (GCT) and oral glucose tolerance tests (OGTT) at specified intervals. Mother and fetal outcomes were compared between the groups with a p value of <0.05 regard as significant. Results: Women with GDM had a significantly higher body mass index (27.8±3.1 kg/m²) compared to the control group (25.4±2.9 kg/m², p<0.001). They also had a higher incidence of cesarean sections (35% versus 20%, p=0.03) and premature rupture of membranes (PROM) (18% versus 8%, p=0.04). Infants of GDM mothers had higher birth weights (3500±500 g versus 3200±450 g, p<0.001) and higher rates of macrosomia (22% versus 8%, p=0.01), neonatal hypoglycemia (15% versus 5%, p=0.01), and respiratory distress (12% versus 4%, p=0.02). Conclusions: GDM increases the risk of PROM, caesarean birth, respiratory distress, hypoglycemia, and macrosomia for the infant and harms the mother and foetus. These findings emphasise early detection and effective GDM therapy.